Hubungan Pengetahuan Dan Sikap Ibu Hamil Dengan Pemeriksaan Kehamilan (Antenatal Care) Pada Masa Pandemi Covid-19 Di Wilayah Kerja Puskesmas Talang Randai Kabupaten Bengkulu Selatan - Sari, Eka Puspita; Gusnidarsih, Vevi; Rahmarianti, Gusni; Fennyria, Dolis Yesti (Gayaku Publisher, 2022)
The purpose of this study was to determine the relationship between knowledge and attitudes of pregnant women with antenatal care during the COVID-19 pandemic in the working area of ​​the Talang Randai Health Center, South Bengkulu Regency. This research is an analytic study with a cross sectional design. The population of this study were all pregnant women who were in the working area of ​​the Talang Randai Health Center with a total sample of 56 people. Data analysis was performed by chi-square test. The results showed that most of them had good knowledge (37.5%), with a positive attitude (76.8%) and with regular examinations (60.7%). The chi square test for the knowledge and examination variables obtained the value of X2 count (14.1) > X2 table (5.591) and the value (0.001) < (0.05) while for the attitude variable obtained the value of X2 count (17.1) > X2 table (3.481) and value (0.000) < (0.05). There is a significant relationship between knowledge and attitudes with pregnancy check-ups in the working area of ​​the Talang Randai Public Health Center, South Bengkulu Regency.